An Emerging Cardiovascular Disease: Takotsubo Syndrome. (30th October 2019) - Moscatelli, Sara; Montecucco, Fabrizio; Carbone, Federico; Valbusa, Alberto; Massobrio, Laura; Porto, Italo; Brunelli, Claudio; Rosa, Gian Marco
Abstract : Takotsubo syndrome (TTS) is a recently identified cardiac disease, which is far from being completely known. The aims of this narrative review are to provide a better understanding of the pathophysiological features of TTS and to update clinical findings in order to improve the management of subjects affected by this syndrome (according to the most recent consensus papers issued by the international scientific societies). We based our search on the material obtained via PubMed up to April 2019. The terms used were "Takotsubo Syndrome and Takotsubo cardiomyopathy" in combination with "heart failure, pathophysiology, complications, diagnosis, and treatment." TTS is a reversible form of ventricular dysfunction usually characterized by akinesia of the apex in the absence of obstructive coronary artery disease. In its initial phase, TTS may be indistinguishable from AMI and is usually triggered by a sudden emotional/physical stressor which abruptly increases catecholamine levels. However, the mechanisms by which catecholamines or other unidentified molecules can cause myocardial dysfunction is unknown. In-hospital stay may be hampered by various life-threatening complications, while data on long-term survival remain scarce and unclear. Furthermore, TTS may sometimes recur. We believe that TTS is clearly a much more complex condition than previously thought. Much remains to be discovered about its pathophysiologic mechanisms, the role of the link between the heart and brain and that of triggering factors and gender, and the reasons why this syndrome displays different phenotypes and sometimes recurs. Undoubtedly, preliminary evidence from pathophysiological studies (mainly genetic studies) has shown promising advances. However, prospective randomized clinical trials are still needed in order to identify and to tailor the best medical treatments for TTS patients.